Pediatric surgical site infection (SSI) following ambulatory surgery: Incidence, risk factors and patient outcomes. (11th August 2022) - Rinke, Michael L.; Bundy, David G.; Heo, Moonseong; Saiman, Lisa; Rabin, Barbara; Zachariah, Philip; Rosenberg, Rebecca E.; DeLaMora, Patricia; Mirhaji, Parsa; Drasher, Michael; Klein, Elizabeth; Obaro-Best, Oghale; et al.
Abstract: Background: Inpatient surgical site infections (SSIs) cause morbidity in children. The SSI rate among pediatric ambulatory surgery patients is less clear. To fill this gap, we conducted a multiple-institution, retrospective epidemiologic study to identify incidence, risk factors, and outcomes. Methods: We identified patients aged <22 years with ambulatory visits between October 2010 and September 2015 via electronic queries at 3 medical centers. We performed sample chart reviews to confirm ambulatory surgery and adjudicate SSIs. Weighted Poisson incidence rates were calculated. Separately, we used case–control methodology using multivariate backward logistical regression to assess risk-factor association with SSI. Results: In total, 65, 056 patients were identified by queries, and we performed complete chart reviews for 13, 795 patients; we identified 45 SSIs following ambulatory surgery. The weighted SSI incidence following pediatric ambulatory surgery was 2.00 SSI per 1, 000 ambulatory surgeries (95% confidence interval [CI], 1.37–3.00). Integumentary surgeries had the highest weighted SSI incidence, 3.24 per 1, 000 ambulatory surgeries (95% CI, 0.32–12). The following variables carried significantly increased odds of infection: clean contaminated or contaminated wound class compared to clean (odds ratio [OR], 9.8; 95% CI, 2.0–48), other insurance type compared to private (OR, 4.0; 95% CI, 1.6–9.8), and surgery on weekend day compared to weekday (OR, 30; 95% CI, 2.9–315). Of the 45 instances of SSI following pediatric ambulatory surgery, 40% of patients were admitted to the hospital and 36% required a new operative procedure or bedside incision and drainage. Conclusions: Our findings suggest that morbidity is associated with SSI following ambulatory surgery in children, and we also identified possible targets for intervention.